STRATEGIC PRIORITIES OF IMPORT SUBSTITUTION IN THE RUSSIAN PHARMACOLOGICAL MARKET - M. Shevkunenko (Вестник Северо-Кавказского федерального университета)
The article deals with the specifics of the functioning of the domestic pharmaceutical market, which is characterized by a stable rate of sales growth, high level of competitiveness and a critical level of import dependence, especially in relation to new innovative drugs. Implementation of the import substitution program in the pharmaceutical industry requires comprehensive state support in the following areas: customs and tariff regulation, quality control of imported drugs, development ofpharmaceutical clusters. Ensuring an acceptable level of economic security of the national economy also requires an increase in the competitiveness of domestic producers not only in domestic but also in global markets, which will provide the population with quality drugs at affordable prices.